A Nação Mura: resistência e reencontro de identidade - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2001)
The study of the situation of contact between Indians and whites in Brazil has merited the attention of several scholars in past and recent times, who, for different motivations, sought to improve the analytical approaches to better explain the phenomenon of contact and its implications for both societies. This paper sought to analyze and understand the current mura organization, based on the results obtained from the analysis of the repercussions in the historical memory of this indigenous nation in relation to the massacres suffered in the past. Our first objective was to verify how the Mura Indians became aware of their historical reality of struggles and exterminations, and, afterwards, to know and study their current organizational structures. Our research was based on reports, videos, bibliographies, and statements brought by Gilberto Mura during his visit to Belém. The Mura indigenous mobilization aiming at the autonomy and self-determination of their people began with the creation of the Coordination of Indigenous Organizations of the Brazilian Amazon - COIAB: Mura Indigenous Council - CIM; Mura Indigenous Festival - FESTIM; Organization of Mura Indigenous Teachers - OPIM; Organization of Mura Indigenous Health Agents - AO SIM; Organization of Mura Indigenous Students - OEIM; Organization of Mura Indigenous Women - UMIM. Differentiated education (OPIM's main objective) is the great leverage of the Mura people in the search for their identity. Despite these limitations, the Mura Nation has a remarkable capacity for resistance.
The Mura Nation: resistance and rediscovery of identity
Keywords: Nação Mura; Indígenas; CNPQ::CIENCIAS HUMANAS::ANTROPOLOGIA